2011
DOI: 10.1259/bjr/92960562
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between mammographic and sonographic findings and prognostic factors in patients with node-negative invasive breast cancer

Abstract: Objectives: The purpose of this study was to correlate sonographic and mammographic findings with prognostic factors in patients with node-negative invasive breast cancer. Methods: Sonographic and mammographic findings in 710 consecutive patients (age range 21-81 years; mean age 49 years) with 715 node-negative invasive breast cancers were retrospectively evaluated. Pathology reports relating to tumour size, histological grade, lymphovascular invasion (LVI), extensive intraductal component (EIC), oestrogen rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
43
5
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 32 publications
10
43
5
3
Order By: Relevance
“…However, it is now widely known that many tumors may have variable posterior acoustic features; new studies have shown that well-defined margins and posterior enhancement are more likely to represent higher grade tumors and negative receptor status (13,15,16). Our results are consistent with these findings and there is a strong statistically significant correlation between these parameters.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, it is now widely known that many tumors may have variable posterior acoustic features; new studies have shown that well-defined margins and posterior enhancement are more likely to represent higher grade tumors and negative receptor status (13,15,16). Our results are consistent with these findings and there is a strong statistically significant correlation between these parameters.…”
Section: Discussionsupporting
confidence: 90%
“…Shin et al (16) showed that masses with circumscribed margins and posterior acoustic enhancement are associated with high grade and negative hormone status. In our study, similar to these results, tumors with circumscribed margins and posterior enhancement were more likely to be triple-negative, high grade, and hormone-receptor negative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22]25 The broadly rounded shape of the masses can be explained by the rapid growth of these tumours that do not produce stromal reaction in breast cancer. 27 However, in contrast with this study and others, [20][21][22][23][24][25] Krizmanich-Conniff et al 26 reported that TNBC was mainly characterized by irregular masses (49%). Moreover, other studies 20,21,25,26 showed that the most common margins of tumour masses on mammography were indistinct (45-55%); however, in this study, the most common mass margins on mammography were circumscribed (37.2%), and less commonly mass margins were microlobulated (25.6%), which was consistent with the study reported by Dogan et al 22 Our results confirmed the findings of previous studies [20][21][22][23][24][25][26] that showed TNBC was less likely to have spiculated margins.…”
Section: Discussioncontrasting
confidence: 87%
“…Characteristics of studies reporting on mammography, breast ultrasound, MRI, and (17,18,70,87,91,(93)(94)(95)(96)(97)(98)(99)(100)(101)(102)(103)(104)(105)(106)(107). Of these, eight articles reported on two imaging modalities: five on both breast ultrasound and mammography (28,33,41,52,56), and three on both 18 F-FDG PET and DWI (70,87), or MRS (91). Table 1 shows the characteristics of the selected studies.…”
Section: Resultsmentioning
confidence: 99%